The Islamic jurisprudence of the Prophet Mohammed in crisis management - Kailan, Noureddine Abdelati (Journal of Islamic Sciences, 2024)
This research comes as an applied study of the prophetic means and methods adopted in getting out of the various crises that the state and individuals experienced in that era, as it sheds light on the mechanisms that the Prophet, may God bless him and grant him peace, used in treating many crises since the beginning of the call for the establishment of the state and compares them with modern methods that have become It is called crisis management methods and is taught as a special art.
Keywords: Crises; Means; Methods; The Prophet Mohammed; Management; Work Team Mechanisms